The Right of the Public Employee to Nominate and be Elected to the Federal National Council in the UAE Legislation "a comparative study - Salem , Mustafa (Journal of Legal Sciences, 2022)
The right to nominate and vote is one of the most important political and constitutional rights of citizens in general and public officials because it is related to the popular will, and as they represent the legal way to exercise sovereignty through the selection of members of Parliament to take over on behalf of the nation. However, these rights, like other rights, are subject to legal regulation. Therefore, the constitutions meant it to give them a great deal of prestige, and the various laws dealt with it by defining the electorate and the conditions that should be fulfilled in the candidate and the voter. Countries differ in their position of the public servant as conditions for membership in the Parliament, with setting controls and restrictions that respond to their exercise in proportion to their sovereignty. Manipulating them leads to problems in the scope of practical application and has caused legal and judicial controversy that appears in every electoral process. We have divided this research into three sections, the first is entitled the public servant and the exercise of the right to candidacy, the second is entitled the public servant and the exercise of the right to vote, and the third is entitled Judicial protection of the public servant’s right to nominate and vote. We have reached several conclusions, the most important of which is that the UAE legislator must stipulate that the employee enjoys citizenship instead of being subordinate to one of the Emirates. And that the UAE legislator was satisfied with the knowledge of reading and writing, and that the UAE legislator permitted the combination of a public job and a local job in addition to many recommendations.